The amino acid sequence of a myotoxic phospholipase from the venom of Bothrops asper - Kaiser, Ivan I. (1990)
A myotoxic, basic phospholipase A2 (pI greater than 9.5) with anticoagulant activity has been purified from the venom of Bothrops asper, and its amino acid sequence determined by automated Edman degradation. It is distinct from the B. asper phospholipase A2 known as myotoxin I [Lomonte, B. and Gutierrez, J. M., 1989, Toxicon 27, 725] but cross-reacts with myotoxin I rabbit antisera, suggesting that the proteins are closely related isoforms. To our knowledge, this is the first myotoxic phospholipase to be sequenced that lacks presynaptic neurotoxicity (iv LD50 approximately equal to 8 micrograms/g in mice). The protein appears to exist as a monomer, contains 122 amino acids, and fits with subgroup IIA of other sequenced phospholipase A2 molecules. Its primary sequence shows greatest identity with ammodytoxin B (67%), a phospholipase A2 presynaptic neurotoxin from Vipera ammodytes ammodytes venom. Hydropathy profiles of B. asper phospholipase and the ammodytoxins also show great similarities. In contrast, even though the amino acid sequence identities between B. asper phospholipase and the basic subunit of crotoxin remain high (64%), their hydropathy profiles differ substantially. Domains and residues that may be responsible for neurotoxicity are discussed.